Optically amplified free-space optical communication systems - Aladeloba, Abisayo Olufemi (2013)
This thesis investigates terrestrial atmospheric FSO communication systems operating under the influence of turbulence-induced scintillation, beam spreading, optical interchannel crosstalk, amplified spontaneous emission noise and pointing errors. On-off keying-non–return-to-zero (OOK-NRZ) and digital pulse position (DPPM) are the modulation schemes used for the calculations.